2015
DOI: 10.1097/pas.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Analysis of H3F3A and H3F3B as a Diagnostic Tool for Giant Cell Tumor of Bone and Chondroblastoma

Abstract: Specific H3F3A driver mutations and IDH2 mutations were recently described in giant cell tumor of bone (GCTB) and H3F3B driver mutations in chondroblastoma; these may be helpful as a diagnostic tool for giant cell-containing tumors of the bone. Using Sanger sequencing, we determined the frequency of H3F3A, H3F3B, IDH1, and IDH2 mutations in GCTBs (n=60), chondroblastomas (n=12), and other giant cell-containing tumors (n=24), including aneurysmal bone cyst, chondromyxoid fibroma, and telangiectatic osteosarcoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
148
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(160 citation statements)
references
References 15 publications
10
148
0
2
Order By: Relevance
“…The diagnosis of giant cell-containing lesions of bone is challenging (15). Cleven et al (15) recently reported that H3F3A mutation analysis appears to be a highly specific, although less sensitive, diagnostic tool for the distinction of GCTB from other giant cellcontaining tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnosis of giant cell-containing lesions of bone is challenging (15). Cleven et al (15) recently reported that H3F3A mutation analysis appears to be a highly specific, although less sensitive, diagnostic tool for the distinction of GCTB from other giant cellcontaining tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Cleven et al (15) recently reported that H3F3A mutation analysis appears to be a highly specific, although less sensitive, diagnostic tool for the distinction of GCTB from other giant cellcontaining tumors. Agaram et al (9) reported that fluorescence in situ hybridization for USP6 break-apart is a useful ancillary tool in the diagnosis of primary aneurysmal bone cysts and can help to distinguish them from giant cell reparative granulomas and other morphologically similar lesions.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4]. This finding has helped to confirm cases with unusual histologic features or metaphyseal location as bona fide giant cell tumors, expanding the clinicopathologic spectrum of the disease [1,4].…”
Section: Musculoskeletal Radiologist Beth Israel Deaconess Medical Cementioning
confidence: 64%
“…[2,4]. This finding has helped to confirm cases with unusual histologic features or metaphyseal location as bona fide giant cell tumors, expanding the clinicopathologic spectrum of the disease [1,4]. H3F3A encodes a replicationindependent histone (H3.3), known to have an epigenetic function regulating other genes; however, the exact mechanistic role of H3F3A mutation in the development of giant cell tumor is unknown.…”
Section: Musculoskeletal Radiologist Beth Israel Deaconess Medical Cementioning
confidence: 95%
“…At least in our experience, IHC is of limited help in difficult cases. However, recent advances in molecular pathology using NGS demonstrated K36M mutations in the H3F3B gene in 95% of chondroblastomas and H3F3A mutations in 92% of giant cell tumors of the bones [12,13] . Both genes encode for histone H3.3 [14] .…”
Section: Overviewmentioning
confidence: 99%